Rancang Bangun Aplikasi E-Library Berbasis Web di SMA Kartika Wirabuana XX-1 Makassar - Muhammad Arfan (Journal on Pustaka Cendekia Informatika, 2024)
The purpose of developing a web-based e-library application at SMA Kartika Wirabuana XX-1 Makassar is to assist library staff in managing book data, member data, loan data, and return data, which are currently handled manually, by transitioning to a computerized web-based system. Additionally, it aims to facilitate members/visitors in searching for reference materials. The current system in the library of SMA Kartika Wirabuana XX-1 Makassar still relies on manual processes, and the information conveyed is inefficient. As a result, library staff often face difficulties in retrieving member data, book data, loan data, and return data. The methodology used in designing this web-based e-library application follows a prototype approach. The outcome of this e-library application development is a software system that enhances the quality and performance of the library at SMA Kartika Wirabuana XX-1 Makassar. A trial conducted using a questionnaire led to the conclusion that respondents' perceptions of the e-library application quality were positive. This is evident from the total percentage of respondents, with the majority (42.3%) falling into the "agree" category.